SISTEM INFORMASI GEOGRAFIS TEMPAT WISATA DI PROVINSI GORONTALO BERBASIS METODE ARCVIEW GIS - F, Farid (Journal Of Software Engineering And Communication, 2025)
Tourism is a strategic sector that plays an important role in improving the regional economy. Gorontalo Province has various potential natural, cultural, and marine tourism destinations to be developed. However, the availability of accurate spatial data regarding the location, accessibility, and distribution of tourist attractions is still very limited. This research aims to design a Geographic Information System (GIS) for Tourism Destinations in Gorontalo Province using ArcView GIS, which can spatially visualize geographic information. The method used is a descriptive approach with the utilization of ArcView GIS software in processing spatial data. The results of this study are in the form of an interactive digital map containing the distribution of tourist locations, detailed information on tourist attractions, and integration of attribute data. With this system, local governments and the community can access tourism information more effectively to support promotion and tourism development planning